Country Proud - Miller, Linda Lael (Toronto, Ontario, Canada : HQN, 2021)
Sheriff Eli Garretts high school sweetheart, Brynne, the girl he betrayed all those years ago, has returned to town and its time to make amends and see what the future might hold, but Brynne wants to remain Elis friend with anything else out of the question until one electric kiss changes everything between them.
Keywords: Ranch life -- Fiction; First loves -- Fiction; Man-woman relationships -- Fiction; Montana -- Fiction; Romance fiction